A compact dipole driven ring base station antenna for full sub‐6 GHz band applications. Issue 11 (5th September 2022) - Lin, Weifeng; Zhang, Jun; Rong, Kang; Huang, Bei
Abstract: In this article, a compact dual‐band antenna is presented for sub‐6 GHz base station applications. The main radiator of the antenna is composed of ring‐shaped dipoles and Y‐shaped dipoles. Broadband impedance matching is achieved by complementarily coupling between the two types of dipoles. The measured results show the bandwidth of the proposed antenna can cover from 2.06 to 3.69 GHz in the low‐frequency band with an around isolation of 30 dB, and cover from 4.79 to 5.02 GHz in the high‐frequency band with an around isolation of 25 dB. The in‐band peak realized gain is 9.12 ± 1.02 dBi. Since the proposed antenna operates at N41, N78, and N79 bands in China, it can be a potential element for full sub‐6 GHz base station applications.